Nilai Moderasi Beragama Sebagai Sumber Belajar Sejarah di Sekolah Menengah Atas - Fitriani, Diah (Prabayaksa: Journal of History Education, 2022)
Indonesia is applying the  principle of unity and brotherhood in spite of all differences that exist in the frame of the motto Bhinneka Tunggal Ika in order to maintain the integration of the nation. However, the fact that differences are an inevitability is sometimes the main source of horizontal conflicts that occur in Indonesia. Religious moderation comes to the core when there is an understanding of extreme religion in the community that lead to disintegration. This article focuses on  providing an understanding of the importance of religious moderation through history subjects in high school. The research method used is literature studies by collecting documents or other literatures related to the title of writing.  The value of religious moderation is essentially part of the character and culture of the Indonesian nation. Internalization of the value of religious moderation through historical learning, among others, upholds the spirit of solidarity, social empathy, and equality of people despite whatever their beliefs. Understanding the value of religious moderation is relevant as a source of historical learning in order to maintain the integrity of the nation in the paradigm of national development.